2019
DOI: 10.1371/journal.pgen.1008233
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolution leading to impaired biofilm formation in invasive Salmonella strains

Abstract: Pathogenic Salmonella strains that cause gastroenteritis are able to colonize and replicate within the intestines of multiple host species. In general, these strains have retained an ability to form the rdar morphotype, a resistant biofilm physiology hypothesized to be important for Salmonella transmission. In contrast, Salmonella strains that are host-adapted or even host-restricted like Salmonella enterica serovar Typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 95 publications
(168 reference statements)
2
46
0
Order By: Relevance
“…We wanted to determine if the host environment in each infection model provided the activating conditions for curli production. We monitored expression of csgD , encoding the curli transcriptional activator [ 14 , 46 ], using a luciferase reporter strain grown in curli-inducing or non-inducing conditions prior to oral infection of streptomycin pre-treated or untreated C57BL/6 mice. At 96 h post-infection, the GI tract, spleen, and liver were removed and imaged; light production was detected in the GI tracts of all infected mice, but not in the liver and spleen ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We wanted to determine if the host environment in each infection model provided the activating conditions for curli production. We monitored expression of csgD , encoding the curli transcriptional activator [ 14 , 46 ], using a luciferase reporter strain grown in curli-inducing or non-inducing conditions prior to oral infection of streptomycin pre-treated or untreated C57BL/6 mice. At 96 h post-infection, the GI tract, spleen, and liver were removed and imaged; light production was detected in the GI tracts of all infected mice, but not in the liver and spleen ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Salmonella and E . coli strains that are associated with invasive disease have generally lost the ability to produce curli and form curli-associated biofilms ([ 46 , 56 ]; summarized in [ 10 ]), which may allow bacteria to spread systemically within the host [ 57 ]. For strains that cause gastroenteritis, studies have shown that curli and flagella are oppositely regulated by the cyclic diguanylate (c-di-GMP) signaling cascade to transition from motility to sessility [ 11 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these genes have been implicated in intestinal colonisation [31,[64][65][66][67][68][69], suggesting that their inactivation in host adapted variants may be associated with a loss of selection for functions no longer required in a reduced host range or where intestinal colonisation is no longer critical to transmission. The sadA and katE, genes are involved in multicellular behaviour, biofilm formation and catalase activity that protects against oxidative stress during high density growth functions, respectively, and are commonly affected by genome degradation in host adapted pathovars of Salmonella [52,70].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…The loss of ability to form biofilm is a common feature of some host-adapted variants of Salmonella enterica (48,49) (Figure 6D). S. Typhimurium strain SL1344 formed moderate biofilm that was dependent on expression of the csgD gene as previously described (48). The mean biofilm formation for ten U288 strains was not significantly different from that of three ST34 strains.…”
Section: S Typhimurium U288 Isolates Have a Longer Doubling Time Andmentioning
confidence: 99%